Experimental Intriguing for Maximization of Useful Life of Spur Gears from Stress Analysis under Multiple Combinations of Pressure Angle - Prithwiraj Jana (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
The various kinds of mechanical transmissions are applied by gears, used in automobile and other industry extensively. Todays, modern world is more competitive day by day. During the product marketing, the service life prediction is one of the important key issue. However, traditional experimental studies focused to predicting contact fatigue life by revealing the stress analysis. This experiment one of the major concerns in the field of various machine modelling, which is to predict the service life of spur gear, used in automobile. This experiment addresses the phenomenon of characterizing the stress analysis of the ground spur gear and to calculate the service life where each of them has different pressure angle and hence, the spur gear with maximum fatigue life is selected.